FREQUENCY OF LARYNGOSPASM IN AWAKE VERSUS DEEP EXTUBATION AFTER INTRANASAL SURGERY: Laryngospasm After Intranasal Surgery - Naqvi, Syed Ehtesham Haider; Khan, Rao Ali Shan; Ahmed, Nadeem; Malik, Usman Eijaz; Rafiq, Muhammad Yasir (Pakistan Armed Forces Medical Journal, 2018)
Objective: To compare the frequency of laryngospasm in awake versus deep extubation after intranasal surgery. Study Design: Randomized controlled trial. Place and Duration of Study: The study was carried out at Combined Military Hospital Rawalpindi which is a tertiary care hospital, after seeking permission from Hospital Ethics Committee. Study was carried out for six months, from Feb 2013 till Aug 2013. Material and Methods: Two hundred and fifty patients fulfilling the inclusion criteria were selected for this study and divided into two groups of 125 each. Patients of group A were extubated fully awake while the patients assigned to group B were extubated during deep anaesthesia. Patients were then monitored closely for 30 minutes to assess whether they developed laryngospasm or not. Results: The mean age in group-A was 23.92 ± 5.01 years and in group-B was 24.16 ± 5.56 years. The mean height in group-A was 169.53 ± 4.74cm and in group-B was 170.42 ± 4.34 cm. The mean weight in group-A was 66.18 ± 6.31 kg and in group-B was 65.67 ± 6.00 kg. In group-A 72% patients were male and 28% were female while in group-B 76% patients were male and 24% patients were female. In group-A 9 (7.2%) patients developed laryngospasm and in group B 6 (4.8%) patients developed laryngospasm. Conclusion: There is no difference in frequency of laryngospasm in awake versus deep extubation after intranasal surgery.